2017
DOI: 10.1111/ejss.12428
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus addition affects soil nitrogen dynamics in a nitrogen‐saturated and two nitrogen‐limited forests

Abstract: Phosphorus (P) availability can affect nitrogen (N) dynamics in forest soil, and this effect might depend largely on the soil N status of forest ecosystems. So far, however, this view has not been well tested among forests with contrasting N status. Here, we used a 6‐year experiment with additions of N and P to evaluate the effects of P availability and its interaction with N availability on soil N dynamics in one N‐saturated and two N‐limited tropical forests in southern China. Soil inorganic N concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…The response of crop yield might be affected directly or indirectly [72,73]. Therefore, the supply of both N and P creat changes in chemical, physical, and biological properties of soil [74,75]. The nitrogen fertilizer has synergetic effect to phosphorus.…”
Section: Available Sources and Forms Nitrogenmentioning
confidence: 99%
“…The response of crop yield might be affected directly or indirectly [72,73]. Therefore, the supply of both N and P creat changes in chemical, physical, and biological properties of soil [74,75]. The nitrogen fertilizer has synergetic effect to phosphorus.…”
Section: Available Sources and Forms Nitrogenmentioning
confidence: 99%
“…Phosphorus addition can affect soil N pools and cycling processes in a variety of ways via different impacts on plant growth and microbial activity (Turner & Wright, 2014). For instance, addition of P decreased N leaching losses and retained more N in plant‐soil ecosystems by promoting plant and microbial growth and N uptake (e.g., Baral et al., 2014; Chen et al., 2017), but it could also increase loss of N through gaseous emissions, such as N 2 O, by stimulating nitrification and/or denitrification processes (Mehnaz, Corneo et al., 2019; Mori et al., 2013). However, reductions in N 2 O emissions were also found in P‐limited ecosystems because of a decline in NO 3 − availability and denitrification (Chen et al., 2016; Mori et al., 2014; Yu et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…[12] Moreover, P applied to soils enhances production of pyridoxal phosphate and promotes aminotransferase activity, accelerating rates of inorganic N forms turnover and organic N forms mineralization. [13] However, some recent studies have shown that phosphate application to the soils has little effect on the bioavailability of soil N [14] or limits the mineralization of organic N. [15] Therefore, the roles of the phosphate fertilization in soil N forms turnover are not fully understood. Furthermore, apart from phosphate addition, tillage and crops are other major factors impacting soil N forms turnover.…”
Section: Introductionmentioning
confidence: 99%